The Pattern of Disseminating Information on The Garut Regency DISPARBUD in The Development of Ecovillage - novianti, Evi; Fajrurrahman, Mufqi; Nugraha, Aat Ruchiat; Khoerunnisa, Lutfi; Rakhmawati, Yuliana (Jurnal Komunikasi, 2022)
Indonesia is known to the world for the tourism it offers. Various approaches to tourism are now emerging over time, and one of the focuses of government development is village-based tourism or ecovillage toursim. The development of this tourist village itself cannot run well if there is no cooperation between the local government and the local community. Therefore, there is a need for communication between the two parties who have a similar vision and mission and are able to work together to develop an ecovillage. This is also what the West Java government and the people of Garut city are doing to develop tourist villages in their area. This study aims to determine the pattern of information dissemination carried out by the Garut Regency Tourism and Culture Office (DISPARBUD) in the development of an ecovillage-based tourism. Using a qualitative descriptive case study method and involving three members of DISPARBUD as the participants, the results of this study indicate that DIPSPARBUD has a simple pattern of disseminating information to local communities regarding the development of ecovillage. This pattern goes through three stages namely; (1) Information distribution (determining communicators, compiling messages, scheduling socialization), (2) Performance reporting (analyzing and responding to the effects of communication, (3) Managing stakeholders (evaluation). With this communication pattern, DISPARBUD seeks to optimize the delivery of information regarding development a tourist village that continues to move forward and is expected to produce many other tourist villages in the future